Learning on the job through collaborative learning: Analysing the appropriation of BIM knowledge in micro-enterprise architectural design companies - Ferreira, R. C.; Rocha, P. N. [UNESP]; Pereira, L. M.; Codinhoto, R.; Fabricio, M. M. (IOP Publishing, 2022)
The lack of Building Information Modelling (BIM) knowledge appropriation by Architectural, Engineering, Construction and Operation (AECO) professionals is often considered one of the main obstacles to successful BIM implementation. Although barriers to implementation have been substantially investigated, a literature review on knowledge appropriation revealed that this area is poorly investigated and biased towards small and medium construction companies. The review also shows that no published research has addressed micro-enterprise design firms, despite these representing approximately 90% of the firms in the AECO sector. In this context, this research investigates whether collaborative learning can be a teaching and learning strategy for appropriating BIM knowledge in architectural design micro-enterprises. The Zone of Proximal Development concept and the Collaborative Learning method were the theoretical lenses to study BIM knowledge appropriation. The research method involved documental analysis of four years of data from a micro-enterprise. The data was classified into vertical collaboration, diagonal collaboration; horizontal collaboration; and individual action. Results show a progressive development of the professionals' (BIM knowledge) autonomy, as they gradually moved from individual action and vertical collaboration relationships to diagonal and horizontal collaboration actions. The evidence indicates that teaching and learning strategies can contribute to the appropriation of BIM knowledge in the context of micro and small companies.